2005
DOI: 10.1074/jbc.m508449200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glycosidic Linkage in Aedes aegypti Chorion Peroxidase

Abstract: Aedes aegypti chorion peroxidase (CPO) plays a crucial role in chorion hardening by catalyzing chorion protein cross-linking through dityrosine formation. The enzyme is extremely resistant to denaturing conditions, which seem intimately related to its posttranslational modifications, including disulfide bond formation and glycosylation. In this report, we have provided data that describe a new type of glycosylation in CPO, where a mannose is linked to the N-1 atom of the indole ring of Trp residue. Through liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…While N-glycosylindoles are encountered in microbial [e.g., staurosporins, 16 rebeccamycins, 17 peroxidase from the mosquito Aedes aegypti, the main vector of dengue and yellow fever, in which α-D-mannose is covalently connected via the N-1 atom of the indole ring. 20,21 NAI-112 Gene Locus. The Actinoplanes DSM24059 locus includes seven genes likely involved in NAI-112 biosynthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While N-glycosylindoles are encountered in microbial [e.g., staurosporins, 16 rebeccamycins, 17 peroxidase from the mosquito Aedes aegypti, the main vector of dengue and yellow fever, in which α-D-mannose is covalently connected via the N-1 atom of the indole ring. 20,21 NAI-112 Gene Locus. The Actinoplanes DSM24059 locus includes seven genes likely involved in NAI-112 biosynthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some earlier workers have already shown that the presence of carbohydrate residues in proteins caused resistance to inactivation mediated urea [33]. In a recent study, Li et al [34] has reported that a peroxidase from Aedes aegypti chorion is extremely resistant to inactivation induced by various denaturing agents [34]. The carbohydrate part of the protein thus contributes towards stabilization of protein against denaturants [35].…”
Section: Discussionmentioning
confidence: 98%
“…Two ions with masses of 367 and 529 Da eluting between 22 and 24 min were detected; the latter decomposed readily to 367 through a loss of 162 Da (hexose) (supplemental Fig. S4), suggesting a cleavage that is typical of O-and N-linked hexoses (20,21). The 367-Da ion and its fragmentation, most notably the 120-Da loss to m/z 247, are identical with standard C 2 -[␣-D-mannopyranosyl]-tryptophan (22,23) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was first reported in pancreatic ribonuclease and since then in over 47 other proteins including notably thrombospondin and complement proteins with the sequence motif WX 1 X 2 W (20,(22)(23)(24)(25)(26). Although the function of this modification remains elusive, mannosylation is known to render the tryptophan more polar and solvent-accessible (23).…”
mentioning
confidence: 99%